Comparative analysis of financial performance during and after the COVID-19 pandemic: Study of state-owned banks listed in the Kompas 100 index - Hadisantoso, Erwin; Anto, La Ode; Arifuddin, Arifuddin; Fuad R, Andi Muhammad; Purnaman, Si Made Ngurah; Ariyfatun, Nurul; Adelia, Gorethi (Edelweiss Applied Science and Technology, 2024)
This study aims to analyze the financial performance of State-Owned Enterprises (BUMN) banks during and after the Covid-19 pandemic listed on the Kompas 100 Index. The analysis of financial performance at these banks uses liquidity ratios, solvency ratios, profitability ratios and Non-Performing Loan ratios. The selection of banks listed on the Kompas 100 Index is expected to be able togeneralized to describe the overall financial performance of banks listed on the Indonesia Stock Exchange (IDX) in facing the Covid-19 pandemic.